EFFICACY OF COMBINATION SOLID DISPERSION TECHNOLOGY ON DISSOLUTION PERFORMANCE OF NALIDIXIC ACID AND CEFDINIR - Maraie, Nidhal Khazaal; Alhamdany, Anas Tarik; Radhi, Ameera Abd (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study was to formulate a new developed solid dispersion containing fixed dose combination of nalidixic acid and cefdinir (500:300 mg) to improve dissolution rate of poorly soluble drugs via a new mechanism as well as the conventional mechanism of solid dispersion represented by the presence of hydrophilic carrier. Methods:Through this objective eight newly developed solid dispersion formulas of fixed dose combination of nalidixic acid and cefdinir (500:300 mg) and (polyethylene glycol (PEG) 6000 and poloxamer 188) in different ratio were prepared, in addition to solid dispersion of each drug alone and simple mixture of individual solid dispersion prepared by means of fusion technique. Moreover, solid dispersions beside pure drugs, simple mixture and physical mixture were characterized by dissolution tests, solubility studies, powder x-ray diffractometry (PXRD), differential scanning calorimetry (DSC), FT-IR spectroscopy (FT-IR) and scanning electron microscopy (SEM). Results: From in vitro dissolution tests, PXRD, DSC, FT-IR, and SEM; it is indicated the presence of a physical complex between cefdinir and nalidixic acid in their solid dispersion containing combination of fixed dose of both drugs. This will affect the crystallinity of the second drug and their dissolution behavior in addition to the conventional mechanism owing to the presence of hydrophilic carrier (poloxamer 188). Conclusion: I was concluded that the newly prepared formula of solid dispersion containing fixed dose combination of nalidixic acid and cefdinir will be promising for higher dissolution profile than that from solid dispersion of each drug alone or simple mixture of individual solid dispersion of each drug. Keywords: Nalidixic acid, Cefdinir, Poloxamer 188, Polyethylene glycol 6000, Combinational solid dispersion, Fusion method.